Heavy metals in system «Delta of Volga - Northern Caspian Sea - E. V. Ostrovscaya; V. F. Brekhovskikh; Z. V. Volkova; S. K. Monakhov; A. A. Kurapov; A. G. Kocharan (Юг России: экология, развитие, 2015)
It is displayed that the composition of heavy metals compounds in water and suspensions in the area of marine and riverine waters mixing undergo natural changes due to sedimentation and transformation. The system “Volga Delta – North Caspian” as a geochemical barrier hampers the transfer of toxic heavy metals forms from the sea to the river, although the content of toxic iron and manganese forms at the marine border of coastal waters can reach up to 30% of total concentration.